МАХНО И БОЛЬШЕВИКИ: ОБСТОЯТЕЛЬСТВА РАСКОЛА (Zaporizhzhia Historical Review, 2021)
The article analyze circumstances of he collapse of the union of the Makhno movement and Bolsheviks. It deconstruct myths of “riot” of Makhno and his military weakness as a reason of the split. Article characterize role of Lenin, Trotsky, Dybenko and other leaders in event, political position of the Makhno’s movement as a main reason of the split, stages of the conflict and its catastrophic results for the Reds.